DESENVOLVIMENTO DE UM MEDIDOR ELETRÔNICO DE ENERGIA ELÉTRICA TRIFÁSICO - Karnikowski, Douglas d. C.; Attuati, Gabriel; Sausen, Paulo S.; Nonemacher, Heriberto B.; Campos, Mauricio d. (Salão do Conhecimento, 2013)
Resumo